2020
DOI: 10.3390/agronomy10020166
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Irrigation and Fertigation on the Yield and Quality of Sugar Beet (Beta vulgaris L.) in a Moderate Climate

Abstract: In Poland, under conditions of the moderate climate and transition between maritime and continental climates, the average rainfall totals of the growing season are in the range of 350–400 mm; however, they are distinguished by great temporal and spatial variability. Climatological studies demonstrate that the drought frequency is approximately 30%. Therefore, under such conditions, irrigation has a supplementary and intervention nature and is applied only when dry periods occur. The aim of this study was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…The increase in the above mentioned traits with the increase of applied levels of nitrogen fertilizer may be attributed to the role of nitrogen in enhancing rapid early growth, encouraging the uptake and utilization of other nutrients including potassium and phosphorous, increasing protein content through synthesize amino acids, and controlling the overall growth of the plant [40,41]. Similar results have been reported by Abdelaal and Tawfik [16], Mekdad [17], Afshar et al [21], and Zarski et al [22]. A moderate supply of nitrogen fertilizer is an essential limiting factor for optimum yield, but the excess in nitrogen fertilizer amounts may result in an increase in root yield with lower sucrose content and juice purity [4][5][6][7].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The increase in the above mentioned traits with the increase of applied levels of nitrogen fertilizer may be attributed to the role of nitrogen in enhancing rapid early growth, encouraging the uptake and utilization of other nutrients including potassium and phosphorous, increasing protein content through synthesize amino acids, and controlling the overall growth of the plant [40,41]. Similar results have been reported by Abdelaal and Tawfik [16], Mekdad [17], Afshar et al [21], and Zarski et al [22]. A moderate supply of nitrogen fertilizer is an essential limiting factor for optimum yield, but the excess in nitrogen fertilizer amounts may result in an increase in root yield with lower sucrose content and juice purity [4][5][6][7].…”
Section: Discussionsupporting
confidence: 75%
“…Increasing the rate of nitrogen fertilizer from 56 to 224 kg/ha led to a linear increase in sugar beet root yield; however, sucrose concentration and purity percentage decreased [21]. Later, Zarski et al [22] recorded a greater yield of sugar and roots in the fertilized sugar beet plants with a high nitrogen rate.…”
Section: Introductionmentioning
confidence: 99%
“…The topdressing in phase of canopy closure is the most common practice over the Europe in sugar beet production. Based on 3-years study in Poland (Bydgoszcz), Žarski et al [58] found that pre-sowing fertilization (160 kg ha −1 N) had on average 84.5 t ha −1 root yield as compared to pre-sowing with top dressing (160 + 40 kg ha −1 N), when root yield was on average 92.1 t ha −1 . In both years, the sucrose content was the highest at pre-sowing N fertilization (45 kg ha −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our own research, reduced tillage combined with simultaneous basic fertilisation and sowing (the ST-OP method) increased soil water reserve in the sowing period for winter and spring crops. This is advantageous because the research site, and much of Poland, are located in areas of frequent rainfall deficits and dry periods [66,67]. Replacing conventional sowing of plants after separate ploughing, to instead use a one-pass technology, resulted in water savings during the soil preparation and sowing periods for winter and spring crops that corresponded to 8.2 mm and 9.7 mm of rainfall, respectively.…”
Section: Discussionmentioning
confidence: 99%